1976
DOI: 10.1901/jaba.1976.9-459
|View full text |Cite
|
Sign up to set email alerts
|

AN ANALYSIS OF MULTIPLE MISPLACED PARENTAL SOCIAL CONTINGENCIES1

Abstract: This study analyzed the training of a mother to modify five subclasses of her attention to her young child's noncompliance with instructions, and also displayed the changes in her child's behavior correlated with these events. Training in four subclasses consisted of teaching the mother to withhold various forms of social attention to her daughter's undesired behavior; training in the fifth subclass involved introduction of a brief room-timeout procedure for noncompliance. The effectiveness of the parent-train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…Accordingly, noncompliance has been the focus of a number of investigations in both laboratory (clinic) and applied (home and school) settings. A number of studies have suggested that child noncompliance is a behavior that is functionally related to other child behaviors which may be members of a 1983,16,[81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] NUMBER I (SPRING 1983) common response class (Budd, Green, & Baer, 1976;Nordquist, 1971;Russo, Cataldo, & Cushing, 1981;Wahler, 1975;Wahler & Nordquist, 1973;Zeilberger, Sampen, & Sloane, 1968). In addition, the response class relationship of compliance among requests has been addressed.…”
mentioning
confidence: 99%
“…Accordingly, noncompliance has been the focus of a number of investigations in both laboratory (clinic) and applied (home and school) settings. A number of studies have suggested that child noncompliance is a behavior that is functionally related to other child behaviors which may be members of a 1983,16,[81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] NUMBER I (SPRING 1983) common response class (Budd, Green, & Baer, 1976;Nordquist, 1971;Russo, Cataldo, & Cushing, 1981;Wahler, 1975;Wahler & Nordquist, 1973;Zeilberger, Sampen, & Sloane, 1968). In addition, the response class relationship of compliance among requests has been addressed.…”
mentioning
confidence: 99%
“…As Budd et al (1976) noted, this omission can have serious impact upon the in tervention chosen. An accurate analysis of behavior problems occurring in the home should include iden tification of family behaviors and activities that co-vary with the child's targeted behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to discover the reason for these earlier results, Budd, Green and Baer (1976) treated a noncompliancy problem by directing intervention toward aspects of the mother's behavior in a single motherchild pair. After observing both mother and child in a request situation, intervention was focused upon five of the mother's behaviors which appeared to co-vary with the child's noncompliance.…”
Section: Reduction Of Inappropriate Behavior Aggression and Noncomplimentioning
confidence: 99%
See 1 more Smart Citation
“…If this method is employed, it would be important to obtain supplemental information regarding child behavior during instructional trials [cf. Budd et al (1976), who measured inappropriate behavior in addition to instruction-completion compliance].…”
Section: Discussionmentioning
confidence: 99%